The Relationship Between Forest Area And Community Income Levels In Indonesia And Issues Related To Both - Suhardi; Gunawan, Cakti Indra; Santosa, Budi (IRDH International Journal of Technology, Agriculture and Natural Sciences, 2025)
This research examines the relationship between the extent of Indonesia's forests and the income levels of the Indonesian population. Using literature review and descriptive analysis of secondary data, this study aims to determine the extent to which Indonesian forests contribute to the economic well-being of the community. The research results show that there is no consistent relationship between the area of Indonesian forests and the income levels of the community. The fluctuating rate of deforestation in Indonesia's forests does not align with the steadily increasing income of the population during the period 2002-2022. The research also revealed a discrepancy in information regarding the contribution of the forestry sector to the national GDP, with percentages varying between 0.66% and 3.11% according to various sources. Through predictive analysis, it is projected that the area of primary forests in Indonesia will increase during the period 2035-2039 and after 2049, while Indonesia's GDP per capita is predicted to continue rising to USD 5,174 by 2050, although it will not yet reach the level of developed countries. This research suggests the need for a more systematic administration system in recording income from the forestry sector, alignment of global forest definitions, and an increase in the contribution of forest products to community welfare while maintaining environmental sustainability.